ANALYSIS OF MACRO AND MICRO ELEMENTS IN THE BIOLOGICALLY ACTIVE SUPPLEMENT “AS-OROM” (Scientific journal of the Fergana State University, 2024)
“AS-OROM” was studied in the argon plasma emission spectrometry (ICP-MS) method, in which elements in the biologically active coupling are bound in an inductive state. The studied “ AS-Oromo” biologically active additive has been shown to contain a total of 61 elements, a natural tendency for the amount of an element to decrease as its mass increases.